Effect of selenium and compost on physiological, biochemical, and productivity of chili under chromium stress - Fahad Ahmad; Sabiha Javied; Kamran Ashraf; Aamir Amanat Ali Khan; Zeeshan Ahmed; Khawar Sultan; Ijaz Ali; Qamar uz Zaman; Ghulam Murtaza; Abd El-Zaher M. A. Mustafa; Mohamed S. Elshikh; Rashid Iqbal; et al. (Scientific Reports)
Abstract In the era of industrialization, chromium (Cr) as a metal poses a substantial threat to the ecosystem. Selenium (Se) is essential for minimizing heavy metal stress in crops and effectively reducing their accumulation in edible plant parts. This research work aimed to evaluate the synergistic effect of compost and Se for alleviation of Cr stress in chili plants. A greenhouse trail was conducted to investigate the individual and combined effects of foliage applied selenium (Na2SeO4 = 3 µM) and soil applied compost (250 mg kg−1, w/w) on the growth, physio-biochemical, antioxidant and of chili grown under varying levels of induced Cr stress (0, 100, and 200 mg kg−1 using K2Cr2O7). Findings revelaed that a significant linear reduction was observed in growth, biomass, and physiological parameters of chili plant with an increasing level of Cr concentrations. Maximum decrease in relative water content (20.04 and 27.21%) and total chlorophyll concentrations (11.73 and 20.57%) and increased in electrolyte leakage (59.14 and 130.52%) was observed at 100 and 200 mg kg−1 of Cr levels in soil in comparison with the control, respectively. Combined application of compost and selenium showed significant increase regardless of Cr concentrations in the soil. Synergistic approach of compost and selenium showed improved growth in comparison with the sole application in limiting the movement and uptake of Cr in the roots and fruits of chili plants. Moreover, improved physiological and antioxidant potential of chili plants helped to cope with higher levels of Cr stress by limiting the lipid peroxidation and membrane damange. The combined use of compost and selenium induces the physio-biochemical defense responses against of the varying levels of Cr stress in chili plants. This promising approach highlights the significant potential for growing chili crop in Cr-contaminated soils to achieve better quality and higher yields.